Child abuse and neglect in Turkey: professional, governmental and non-governmental achievements in improving the national child protection system. (November 2013) - Akco, Seda; Dagli, Tolga; Inanici, Mehmet Akif; Kaynak, Hatice; Oral, Resmiye; Sahin, Figen; Sofuoglu, Zeynep; Ulukol, Betul
Abstract : Since ratification of the United Nations Convention on the Rights of the Child in 1995, significant efforts were made in Turkey to improve protection of children from abuse and neglect. The government took steps to amend relevant laws. Several state departments recognized the need for professional in-service training of relevant governmental agency staff. University hospitals established numerous hospital-based multidisciplinary child protection centres. The government established an Interministerial Higher Council, which has been overseeing the foundation of 13 child advocacy centres for a multidisciplinary and interagency response to child sexual abuse. In addition to undertaking research, non-governmental organizations contributed to this process by instituting professional and public education. These ground-breaking developments in the last decade give promise of even further improvement in the national child protection system from investigative, child protective and rehabilitative perspectives.